Non-surgical instrumentation associated with povidone-iodine in the treatment of interproximal furcation involvements (Journal of Applied Oral Science, 2010)
OBJECTIVE: The aim of this controlled clinical trial was to evaluate the effect of topically applied povidone-iodine (PVP-I) used as an adjunct to non-surgical treatment of interproximal class II furcation involvements. MATERIAL AND METHODS: Thirty-two patients presenting at least one interproximal class II furcation involvement that bled on probing with probing pocket depth (PPD) >;5 mm were recruited. Patients were randomly chosen to receive either subgingival instrumentation with an ultrasonic device using PVP-I (10%) as the cooling liquid (test group) or identical treatment using distilled water as the cooling liquid (control group). The following clinical outcomes were evaluated: visible plaque index, bleeding on probing (BOP), position of the gingival margin, relative attachment level (RAL), PPD and relative horizontal attachment level (RHAL). BAPNA (N-benzoyl-L-arginine-p-nitroanilide) testing was used to analyze trypsin-like activity in dental biofilm. All parameters were evaluated at baseline and 1, 3 and 6 months after non-surgical subgingival instrumentation. RESULTS: Six months after treatment, both groups had similar means of PPD reduction, RAL and RHAL gain (p>;0.05). These variables were, respectively, 2.20±1.10 mm, 1.27±1.02 mm and 1.33±0.85 mm in the control group and 2.67±1.21 mm, 1.50±1.09 mm and 1.56±0.93 mm in the test group. No difference was observed between groups at none of the posttreatment periods, regarding the number of sites showing clinical attachment gain >;2 mm. However, at 6 months posttreatment, the test group presented fewer sites with PPD >;5 mm than the control group. Also at 6 months the test group had lower BAPNA values than control group. CONCLUSION: The use of PVP-I as an adjunct in the non-surgical treatment of interproximal class II furcation involvements provided limited additional clinical benefits.